Efektivitas Media Edukatif Video Sanggul Tradisional Siswa SMK Negeri 06 Semarang - Anggraeni, Nelly Setyowati; Krisnawati, Maria; Wahyuningsih, Sri Endah; Widowati, Trisnani (Universitas Negeri Semarang, 2025)
Lack of creativity is caused by students' lack of knowledge and lack of interest in reading books and looking for references from other sources. A monotonous bun turns out to be an indicator of a student's lack of creativity, and is often the same as several other students. The researcher decided to carry out research on the effectiveness of educational media on traditional bun videos on traditional bun students at SMK Negeri 06 Semarang with the basic competencies of bun gelung malang, bun pusung tagel and bun ukel konde which have the advantage of making interesting video tutorials.The method used in this research is R&D with the ADDIE model which consists of analysis, design, development, implementation and evaluation stages. This research method uses data collection techniques in the form of a Likert scale questionnaire and is analyzed using quantitative descriptive techniques. This research was implemented at SMK Negeri 06 Semarang with a total population of class XI majoring in beauty engineering with a sample of 60 studentsThe results of this research show (1) Development research using the ADDIE model produces a learning media product in the form of traditional bun video educational media that is suitable for use. (2) Feasibility results from the validity test using Aiken V. In terms of material feasibility, an Aiken score of 0.783 was obtained and media feasibility with an Aiken score of 0.719 in the valid category (3) Effectiveness test results using a sample t-test with significant results and t value = 6.847 > t table (df-2) = 2,048 (4). and the N Gain test results show that the N-Gain in the control class is 22.9% in the low category and the N-Gain in the experimental class is 62.5% in the medium category. So that educational media is effective in improving learning outcomes for beauty system students.